Modeling Strategic Electricity Storage: The Case of Pumped Hydro Storage in Germany - Wolf-Peter Schill; Claudia Kemfert (Energy Journal, 2011)
We study the strategic utilization of storage in imperfect electricity markets. We apply a game-theoretic Cournot model to the German power market and analyze different counterfactual and realistic cases of pumped hydro storage. Our main finding is that both storage utilization and storage-related welfare effects depend on storage ownership and the operator's involvement in conventional generation. Strategic operators generally under-utilize owned storage capacity. Strategic storage operation may also lead to welfare losses, in particular if the total storage capacity is controlled by an oligopolistic generator that also owns conventional generation capacity. Yet in the current German situation, pumped hydro storage is not a relevant source of market power.
Additional information: This is a postprint of an article published in Energy Journal 32 (2011), 3, p. 59-87, available online at: http://dx.doi.org/10.5547/ISSN0195-6574-EJ-Vol32-No3-3
Keywords: Q40; Q41; L13; D43; 330; Electric Power Markets; Storage; Market Power; Nash-Cournot; Elektrizität; Wasserversorgung; Wasserwirtschaft; Deutschland